The Ethics of Motion : Self-Preservation, Preservation of the Whole, and the 'Double Nature of the Good' in Francis Bacon - Manzo, Silvia (2016)
This chapter focuses on the appetite for self-preservation and its central role in Francis Bacon's natural philosophy. In the first part, I introduce Bacon's clas- sification of universal appetites, showing the correspondences between natural and moral philosophy. I then examine the role that appetites play in his theory of motions and, additionally, the various meanings accorded to preservation in this context. I also discuss some of the sources underlying Bacon's ideas, for his views about pres- ervation reveal traces of Stoicism, Telesian natural philosophy, the natural law tradi- tion, as well as late-scholastic ideas. Bacon assumes the existence of two kinds of preservation: self-preservation and preservation of the whole. The appetite through which the whole preserves itself overpowers individual appetites for self- preservation. In Bacon's theory of motions, the primacy of global preservation - that is, the preservation of the whole - is evidenced by the way matter resists being annihilated, while self-preservation at a local and particular level is revealed through other kinds of motion. Bacon's notion of appetite reflects a specific metaphysics of matter and motion, in which the preservation of natural bodies follows teleological patterns shared by both nature and humanity: the preservation of the whole is the highest goal, both in moral and natural philosophy. In this chapter, I argue that in Bacon's natural philosophy different kind of things, including nature and humans, are ruled by patterns that are constitutive of correlated orders, neither of which is reducible to the other: there is no priority of the natural order over the moral, or vice versa. Thus, at a more general level, both are expressions of the same type of divinely imposed, law-like behaviour.